Reduction in mortality associated with secondary cytomegalovirus prophylaxis after solid organ transplantation. Issue 3 (30th March 2018) - Serrano‐Alonso, M.; Guillen‐Grima, F.; Martin‐Moreno, P.; Rabago, G.; Manrique, J.; Garcia‐del‐Barrio, M.; Reina, G.; Torre‐Cisneros, J.; Fernandez‐Alonso, M.; Herrero, J.I.
Abstract: Background: Cytomegalovirus (CMV) is the most important viral pathogen in solid organ transplant (SOT) recipients. The role of secondary CMV prophylaxis in this population remains unclear. Methods: Retrospective cohort study in a single center. SOT recipients treated for CMV infection from 2007 to 2014 were studied to determine the efficacy and safety of secondary prophylaxis and its impact on graft loss and mortality. The outcome variable was CMV replication in the first 3 months after the end of therapy. Secondary variables were crude mortality and graft lost censored at 5 years after transplantation. Propensity score for the use of secondary prophylaxis was used to control selection bias. Results: Of the 126 treated patients, 103 (83.1%) received CMV secondary prophylaxis. CMV relapse occurred in 44 (35.5%) patients. The use of secondary prophylaxis was not associated with fewer relapses (34.0% in patients with prophylaxis vs 42.9% in those without prophylaxis, P  = .29). After a mean follow‐up of 32.1 months, graft loss was not different between both groups but patient mortality was significantly lower in patients who received secondary prophylaxis (5.8% vs 28.6%, P  = .003). Conclusion: Secondary prophylaxis did not prevent CMV infection relapse but it was associated with improved patient survival.